Preventive role of aminophylline on renal vascular changes among shock wave lithotripsy patients - Sarpal, Rajeev; Goyal, Mamta; Pathak, Priyank; Ganesamoni, Raguram; Sabnis, Ravindra Bhalchandra (International Surgery Journal, 2018)
Background: Shock wave lithotripsy is commonly used procedure for the treatment of urinary calculi which has revolutionized the treatment of urinary lithiasis since 19801. This study was undertaken to study the effect of aminophylline as a protective measure in preventing renal microvascular damage following SWL through RI in a prospective randomised controlled fashion. Methods: This prospective randomized experimental case control study was conducted from September 2010 to August 2011 at a tertiary care urological hospital. Total 52 patients with less than 2cm size renal stones were divided in two groups of 26 patients each. Results: Stone characteristics as site, size, laterality and Hounsfield units (HU) were comparable in both the groups. Mean RI of diseased and contralateral kidneys in group ‘A’ showed statistically significant rise at 4 hours, 12 hours and 24 hours, with no significant difference in RI at one week and one month. Complete stone clearance was achieved in immediate post-operative period in 88.46% of cases in group A and 96.1% in group B. Conclusions: Author conclude protective effect of aminophylline over renal vascular injury in shock wave lithotripsy patients in form of early return of resistive index values toward baseline.